2015
DOI: 10.1124/mol.115.100867
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic Attenuates GLI Signaling, Increasing or Decreasing its Transcriptional Program in a Context-Dependent Manner

Abstract: The metalloid arsenic is a worldwide environmental toxicant, exposure to which is associated with many adverse outcomes. Arsenic is also an effective therapeutic agent in certain disease settings. Arsenic was recently shown to regulate the activity of the Hedgehog (HH) signal transduction pathway, and this regulation of HH signaling was proposed to be responsible for a subset of arsenic's biologic effects. Surprisingly, these separate reports proposed contradictory activities for arsenic, as either an agonist … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…These studies focused on the active forms of GLI. A recent report suggested context-dependent arsenic attenuation of both GLI activator and repressor forms (Li et al, 2016). Pan inhibition may explain why arsenic can be carcinogenic where GLI repressor plays a dominant role (Fei et al, 2010).…”
Section: Reviewmentioning
confidence: 99%
“…These studies focused on the active forms of GLI. A recent report suggested context-dependent arsenic attenuation of both GLI activator and repressor forms (Li et al, 2016). Pan inhibition may explain why arsenic can be carcinogenic where GLI repressor plays a dominant role (Fei et al, 2010).…”
Section: Reviewmentioning
confidence: 99%
“…On the other hand, GLI1 has been shown to be a target of arsenic trioxide (ATO), which is FDA approved for the therapy of adult patients with acute promyelocytic leukaemia (APL) 38 . A phase I trial investigating the co-administration of ATO and 5-Fluorouracil/Leucovorin in patients with advanced/relapsed colorectal cancer showed that ATO was well tolerated and that in some patients it was associated with down-regulated thymidylate synthase expression, indicating a therapeutic response, and increased survival 39 ; a later study investigated GLI1 levels in biopsies from the said clinical trial and found that it resulted to be down modulated after ATO administration 40 .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, our laboratory found that subacute arsenic treatment in SKH‐1 hairless mice disrupts the Hippo signaling pathway, leading to the disruption of tight/adherens junctions . Yap nuclear translocation and transcription of Yap target genes, including Gli2 , which encodes an important transcription factor in Sonic hedgehog signaling, are considered important in various delayed cutaneous manifestations, including the skin cancers …”
Section: Chemical Warfare and Industrial Arsenicalsmentioning
confidence: 99%
“…47 Yap nuclear translocation and transcription of Yap target genes, including Gli2, which encodes an important transcription factor in Sonic hedgehog signaling, are considered important in various delayed cutaneous manifestations, including the skin cancers. 54,55 Arsine gas Arsine is a colorless, non-irritating gas with a garliclike order at concentrations of 0.5 ppm or above. 56 It is the most toxic form of inorganic arsenic, and the inhalation of small amounts may be fatal.…”
Section: Molecularmentioning
confidence: 99%